(untitled) - Escott, John. (Oxford, England, 2008)
Content: Come with us to London - a city as old as the Romans, and as new as the twenty-first century. There are places to go - from Oxford Street to Westminster Abbey, from Shakespeare's Globe Theatre to Wimbledon Tennis Club. And things to do - ride on the London Eye, visit the markets, go to the theatre, run in the London Marathon. Big, beautiful, noisy, exciting - that's London.
Keywords: London (England),London; Guidebooks.,Sách hướng dẫn du lịch